PENINGKATAN KETERAMPILAN SOSIAL MELALUI BERMAIN PERAN PADA KELOMPOK B DI PAUD TELKOM SINGARAJA - Tita Norma Gita; Mutiara Magta (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2020)
The purpose of this study was to improve social skills through role playing in group B in PAUD Telkom Singaraja. This research is a classroom action research (CAR) which is carried out in 1 action cycle with 5 meetings. The subjects of this study were children of B2 PAUD Telkom Singaraja group in the academic year 2017/2018, as many as 29 students. Data collection to find out the improvement of social skills through role playing activities in this study was carried out using role playing activities with the theme of the profession. Furthermore, the data was analyzed with descriptive-qualitative and quantitative-descriptive techniques. The results of the study can be seen from the development observations in each cycle, namely the condition of BSB Pre-Actions amounting to 2 children (6.89%) and still less than the specified success indicators. The results of the research action of BSB meeting 5 Cycle number were 27 children (93.1%) already in very good criteria based on predetermined success indicators. thus role playing can improve social skills in PAUD Telkom Singaraja.